Proyecto para la valoración del impacto económico-financieroa una distribuidora de tamaño pequeño por la implementación de un nuevo sistema de distribución - Panta Mera, Fatima Virginia (2009)
In the present research we obtained information about the mechanical behavior of concretes of high resistance analyzing laboratory information. We developed concretes using Portland cement, silica fume and additives High-Range Water Reducer. Later diverse types of destructive and not destructive tests were realized according to the ASTM Procedure, to evaluate the resistance of the concrete and then to be able to correlate them. It is known that the concrete of high Resistance is used where it is important to reduce dimensions for the structural elements for design reasons, which also reduces also the quantity of steel and in this manner the permanent dead-weight capacity which diminishes often the total cost of the structure. This study can be taken as a technical document of reference in order that companies and institutions related to the civil engineering activity can apply concretes of high resistance in the different structures using local materials. The present work has its field of action in prefabricated units of concrete, in the construction of superstructures as buildings of great height, bridges, in constructions where a premature remove of formwork is needed, to satisfy specific needs of special applications as for example permanence, module of elasticity and resistance to the flexion.